2020
DOI: 10.1096/fj.201902697rr
|View full text |Cite|
|
Sign up to set email alerts
|

JAK3 restrains inflammatory responses and protects against periodontal disease through Wnt3a signaling

Abstract: Homeostasis between pro-and anti-inflammatory responses induced by bacteria is critical for the maintenance of health. In the oral cavity, proinflammatory mechanisms induced by pathogenic bacteria are well-established; however, the anti-inflammatory responses that act to restrain innate responses remain poorly characterized. Here, we demonstrate that infection with the periodontal pathogen P. gingivalis enhances the activity of JAK3 in innate immune cells, and subsequently phospho-inactivates Nedd4-2, a ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Interestingly, we observed negative regulatory relationships between the NF‐κB and Wnt/β‐catenin signalling pathways in periodontal inflammatory microenvironments. A recent study has found that the activation of the Wnt/β‐catenin pathway can inhibit NF‐κB activity and reduce inflammation, while the inhibition of the Wnt signalling pathway increases NF‐κB activity (Lu et al, 2020). These results are consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed negative regulatory relationships between the NF‐κB and Wnt/β‐catenin signalling pathways in periodontal inflammatory microenvironments. A recent study has found that the activation of the Wnt/β‐catenin pathway can inhibit NF‐κB activity and reduce inflammation, while the inhibition of the Wnt signalling pathway increases NF‐κB activity (Lu et al, 2020). These results are consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the EGFR tyrosine kinase inhibitory resistance pathway may provide a useful biomarker for H. cuspidatus asthma treatment efficacy. In clinical research, the JAK3 inhibitor tofacitinib has been widely used to treat a variety of diseases, and tofacitinib demonstrates potential as an alternative therapy for asthma [ 38 ]. JAK3 is an upstream signaling pathway of STATs, whose activation promotes the expression of STATs, an airway inflammatory target involved in the pathogenesis and development of asthma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirmed that the activation of the Wnt3a/β‐catenin signalling pathway inhibited the Emmprin/MMP‐2 pathway via the coculture of permanent oral epithelial cells/human gingival fibroblasts, which helped reduce the damage to periodontal tissues in periodontitis (X. Liu et al, 2018). L. Lü et al (2020) found that decreased degradation of Wnt3a inhibited the development of periodontitis. Porphyromonas gingivalis infection increased the activity of JAK3 (Janus kinase 3) in innate immune cells, which reduced the ubiquitination degradation of Wnt3a, inhibited the production of pro‐inflammatory factors, such as tumour necrosis factor α (TNF‐α), interleukin‐6 (IL‐6), and interleukin‐12P40 (IL‐12P40), and finally inhibited the development of periodontitis (L. Lü et al, 2020).…”
Section: Wnts and Periodontitismentioning
confidence: 99%
“…L. Lü et al (2020) found that decreased degradation of Wnt3a inhibited the development of periodontitis. Porphyromonas gingivalis infection increased the activity of JAK3 (Janus kinase 3) in innate immune cells, which reduced the ubiquitination degradation of Wnt3a, inhibited the production of pro‐inflammatory factors, such as tumour necrosis factor α (TNF‐α), interleukin‐6 (IL‐6), and interleukin‐12P40 (IL‐12P40), and finally inhibited the development of periodontitis (L. Lü et al, 2020). Similarly, X. Zhang et al (2017) found that parthenolide (PTL) promoted the differentiation of hPDLCs in an inflammatory environment partially by antagonising the inhibitory effect of TNF‐α on Wnt/β‐catenin signal transduction.…”
Section: Wnts and Periodontitismentioning
confidence: 99%